Efecto del ácido abscísico en banano de exportación (Musa AAA var. Gran Enano), en Valle de la Estrella, Limón, Costa Rica - Claderón-López, Kenneth Francisco (Instituto Tecnológico de Costa Rica, 2019)
Physiological damage in clusters of Musa AAA var. Great Dwarf can generate losses of up to 18% of production per hectare. Studies have indicated that the use of abscisic acid improves calcium movement in both leaves and fruit. Being the stain of maturity and cracks of the shell caused mainly by calcium deficiencies, applications of abscisic acid are applied to leaves and clusters to determine the behavior of the stain of maturity and cracks of peel in mature. The results obtained with the ABA applications to the selected clusters differences between treatments (p-value = 0.012), contrary to the results obtained for the ABA applications to the foliage where no treatment effect was obtained (p-value = 0.9314 ). The presence of peel cracks in the mature state when the ABA was applied to the cluster without treatment effect (p-value = 0,1701), but if a decrease as the ABA concentration increased. The same was not found when ABA was applied to the foliage (p-value = 0.2759), since it is adjusted the ABA concentrations were increased, the cracks in the shell increased. The productive parameters were not affected by ABA applications. One of the objectives was to observe the effect of ABA on the growth of the child. Applications to foliage (p-value = 0.3522) did not affect the treatment, there was no decrease in the growth of the child. The applications of ABA to the cluster had no effect on the decrease of the growth of the mother plant's son, since the applications were directed to the cluster. It was detected that in the applications of ABA to the clusters there was an increase in the weight of the cluster as ABA concentration is estimated (p-value-0.0178) but it is attributed to the average number of hands per cluster and not due to ABA. ABA applications to foliage had no treatment effect (0.6256). Therefore, it is concluded that ABA applications at the time of September do not detect the effect of the treatment, but if the cracks are determined in cluster applications.
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía, 2019.
Keywords: Producción agrícola; Exportación; Economía; Agricultura; Frutas; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production